Regional Unemployment Rates and Total Economic Growth in Canada, 1953-1968 - Donner, Arthur (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
In this article the author tests the hypothesis that the process of general economic growth in Canada has an unequal impact on regional economic activity.